USE AND ADHERENCE TO PERSONAL PROTECTIVE EQUIPMENT BY RESIDENTS: VALIDATION OF A MEASURING INSTRUMENT - Dutra, Herica Silva; Assis, Camila Cristina Gregório de; Laurindo, Cosme Rezende; Costa, Kelly Aline Rodrigues; Pereira, Adriane Barbara; Lanza, Fernanda Moura; Coelho, Angélica da Conceição Oliveira (Cogitare Enfermagem, 2023)
Objective: To validate the measuring instrument that assesses healthcare residents’ use and adherence to personal protective equipment. Method: Methodological study developed in a virtual environment between August 2020 and March 2021 with primary care and hospital residents from the five regions of Brazil. The participants answered the adapted version of the "P.P.E.-PHC" for residents. Confirmatory factor analysis was used to validate the instrument. Results: 227 residents took part, the majority of whom were cis women (82.8%), worked in the Southeast region (58.1%), and in-hospital care (47.6%). The structure in eight domains (cap, gloves, safety behavior, N95 mask, hand hygiene, apron/coat, surgical mask, goggles/face shield) was confirmed. Only two items with a factor load of less than 0.5 were kept. Conclusion: The tool is valid for measuring residents’ use of and adherence to personal protective equipment, which helps to guide training and occupational safety.